2022
DOI: 10.1152/jn.00458.2021
|View full text |Cite
|
Sign up to set email alerts
|

Can moving in a redundant workspace accelerate motor adaptation?

Abstract: Variability in behavior can be a manifestation of unwanted noise. However, variability can also reflect exploration, and benefit learning. For example, it has been shown that inter-individual differences in motor learning can be partly explained by differences in movement variability at baseline. Here, we examined whether permitting vs. constraining movement variability via target shape alters motor learning rate in one and the same individual. Healthy young subjects reached to visual targets in 2D space with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, in the context of mastering tennis, precise targeting of various areas of the court and executing shots from different locations are perfected through many rounds of practice. Previous studies have demonstrated that the outcome of motor learning depends on the motor exploration process associated with the learning methods (1)(2)(3). However, the effect of the motor exploration process on the acquisition of new motor skills from scratch remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the context of mastering tennis, precise targeting of various areas of the court and executing shots from different locations are perfected through many rounds of practice. Previous studies have demonstrated that the outcome of motor learning depends on the motor exploration process associated with the learning methods (1)(2)(3). However, the effect of the motor exploration process on the acquisition of new motor skills from scratch remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Continual exploration may be a beneficial strategy in a dynamic or uncertain environment. 19 Promiscuous songbirds explore by injecting greater levels of variability in the pitch of their tune to attract several mates. 20,21,22,23,24 Likewise, movement variability may facilitate the ability to find the most successful motor action.…”
Section: Introductionmentioning
confidence: 99%
“…Past work has highlighted that humans are more variable along such redundant solution manifolds [3,5,6,10,11,[14][15][16], which may reflect an exploratory mechanism that is continually searching for the most successful action [17,18]. Continual exploration may be a beneficial strategy in a dynamic or uncertain environment [19].…”
Section: Introductionmentioning
confidence: 99%